La importancia de las barreras vivas en los sistemas agropecuarios de los valles - Sims, B.; Romney, Dannie L.; Rodríguez, F. (International Maize and Wheat Improvement Center, 2001)
This paper describes the history of the destruction of the sustainable crop-livestock systems of the high altitude areas of Bolivia. One result of this is the shortage of forage for livestock. One possible solution to the soil degradation on sloping lands is the establishment of live barriers with phalaris grass. The information available on the productivity and nutritive value of this species is summarized and it's value as a source of forage is calculated. Preliminary information on the requirements of draught oxen in the interandean valleys allows the calculation of anual requirements of Metabolizable Energy,. and it is concluded that live barriers together with other sources of forage have the potential to make an important contribution to livestock nutrition.